ANALISIS SWOT MANAJEMEN TAMAN PENDIDIKAN AL QURAN MASJID AL AZHAR KOMPLEKS UNIVERSITAS NEGERI PADANG - jalius jalius (Universitas Negeri Padang, 2014)
This study was done at TPQ Al-Azhar using the SWOT framework. The goal is to describe the strengths, weaknesses, opportunities and threats of management. The approach is descriptive qualitative. Data obtained from the management, student’s parent and documentation of data. The result of study show that the strength lies in the good management, the weakness are there is no long-term planning as well as extracurricular not followed by the majority of students. The opportunities are government support in the form of local regulations and the desire of public for TPQ that have a certain quality. The threats is the emergence of competitor institutions. Implementation of progressive management absolute run. The suggestion are to make long-term plans, provide security personnel, school car and perform socialization to the community and establish partnerships with other agencies or institutions that allow to contribute.